Introduction to Alternative Fuels and Their Utilization Strategies in Internal Combustion Engines - Singh A.P.; Mustafi N.N.; Sharma Y.C.; Agarwal A.K. (My University, 2025)
Increasing global demand of fossil fuel and harmful pollutant emitted by petroleum-fuelled internal combustion (IC) engines are two major concern for Indian transport sector, which require an immediate action to explore the alternative fuels such as biofuels, biodiesel, alcohols, etc. This book is based on such alternative fuels and covers different aspects of alternative fuels such as production and utilization. This book is divided into four sections. First section is based on introduction of alternative fuels and their utilization strategies in different type of IC engines. Second section deals with biofuel production from different sources such as agricultural waste, organic waste, microalgae, etc. Third section of this book is based on utilization of alternative fuels in engines. This section shows the potential of different alcohols and ethers to be utilized in engines. Last section of this book is based on advance topics related to alternative fuels. Overall, this book presents an overall picture of alternative fuels and shows the potential of alternative fuels for sustainable transport sector. © 2020, Springer Nature Singapore Pte Ltd.